Classification of homogeneous Fourier matrices - Singh, G. (Algebra and Discrete Mathematics, 2019)
Modular data are commonly studied in mathematics and physics. A modular datum defines a finite-dimensional representation of the modular group SL₂(Z). In this paper, we show that there is a one-to-one correspondence between Fourier matrices associated to modular data and self-dual C-algebras that satisfy a certain condition. We prove that a homogenous C-algebra arising from a Fourier matrix has all the degrees equal to 1.